2012
DOI: 10.1258/td.2012.110445
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus – still a scourge in the 21st century: a paediatric hospital-based study in India

Abstract: Tetanus remains endemic in India. A retrospective hospital-based study was conducted to review the profile of all children admitted with diagnosis of tetanus between January 2009 and December 2010. A total of 140 cases of tetanus were admitted; 45 cases of neonatal tetanus (NT) and 77 cases of post-neonatal tetanus (PNT) were studied. Age of presentation of NT was 9.4 ± 1.2 days. Home-delivered children accounted for 86.7% of cases, with 77.8% being attended by untrained birth attendants. Unimmunized mothers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 2 publications
2
15
1
Order By: Relevance
“…Similarly, Mishra et al too found sepsis to be strongly associated with mortality. 12 Many studies have found pneumonia (aspiration or ventilator associated) to be a risk factor for mortality. 12 However, our study did not conclude the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Mishra et al too found sepsis to be strongly associated with mortality. 12 Many studies have found pneumonia (aspiration or ventilator associated) to be a risk factor for mortality. 12 However, our study did not conclude the same.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features seen (trismus, spasms, hypertonia, and fever) in our study (as described in ►Table 3) are comparable to other similar studies. 4,9,10,12 All our patients received HTIG (6,000 IU), complete course of tetanus toxoid immunization, metronidazole, and amoxycillin-clavulanate. Some patients required higher antibiotics, while some required inotropes.…”
Section: Discussionmentioning
confidence: 99%
“…Most tetanus occurs in rural areas. Mortality is highest in patients not admitted to hospital, and delayed admission to hospital is associated with worse outcomes in neonatal tetanus 62–64. Facilities for ventilation and intensive care are associated with improved outcome in both neonatal and non-neonatal tetanus 45,65,66.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Severe advanced tetanus cases call forcare with sedation, airway protection and well-ordered ventilation. 10,11 Autonomic dysfunction is common with events of tachycardia, raised blood pressure and sweating. 12 nervoussystem variability are recognized to be the roots of death with tetanus.…”
Section: Introductionmentioning
confidence: 99%